Existence and uniqueness analysis of Atangana-Baleanu fractional order network model of Noro virus - Otugene*, V.B.; Agina, P.C.; Edogbanya, H.; Digwo§, D.C. (International Journal of Mathematical Analysis and Modelling, 2023)
This manuscript is concerned to the study of noro virus model and its complications with the Atangana-Baleanu fractional order derivative which is a new approach for such type of biological models. Further for the corresponding results, existence and uniqueness of the solution is examined by engaging the ﬁxed point theory and Pichard Lidelof approach